Analisis Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan Pemerintah Daerah Kabupaten Bengkalis Dalam Persfektif Islam - Sri Rahmany; Fatimah Fatimah (LPPM ISNJ Bengkalis, 2020)
Regional Autonomy requires the Regional Government to be able to provide the best service to the community. One form of the service is to provide transparent financial information. The purpose of this research was to determine the internal control system on the quality of Bengkalis Regency's financial statements reviewed according to the Islamic perspective. This research uses qualitative analysis with descriptive methods. The results showed that the internal control system can minimize the occurrence of fraud/errors both in recording and presenting financial statements as evidenced by the monitoring of accounting records so that the resulting financial statements can be as desired and accountable.